2008
DOI: 10.1007/s10484-008-9071-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Oscillations in Quantitative EEG Measured During a Continuous Performance Task

Abstract: The objective of the present investigation was to determine if cyclic variations in human performance recorded during a 30 min continuous performance task would parallel cyclic variations in right-hemisphere beta-wave activity. A fast fourier transformation was performed on the quantitative electroencephalogram (qEEG) and the performance record of each participant (N = 62), producing an individual periodogram for each outcome measure. An average periodogram was then produced for both qEEG and performance by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…It is well established that extended time on task leads to degradations in performance (e.g., Davies & Parasuraman, 1982;Van der Hulst, Meijman, & Rothengatter, 2001). There is also evidence for systematic oscillations in alertness over relatively short periods of a couple of minutes (Arruda, Zhang, Amoss, Coburn, & Aue, 2009). In addition, when people note that they have drifted well off the road, it is likely that they experience a transient spike in alertness, which would allow them to reestablish control.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that extended time on task leads to degradations in performance (e.g., Davies & Parasuraman, 1982;Van der Hulst, Meijman, & Rothengatter, 2001). There is also evidence for systematic oscillations in alertness over relatively short periods of a couple of minutes (Arruda, Zhang, Amoss, Coburn, & Aue, 2009). In addition, when people note that they have drifted well off the road, it is likely that they experience a transient spike in alertness, which would allow them to reestablish control.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our finding that attentional state ratings and prestimulus alpha power co-vary strongly when smoothed with a sliding window size of several minutes’ worth of trials is in agreement with this literature. In addition, many studies investigating periodicities in reaction times and error rates in detection tasks have reported cycle times in the range of 2–10 min (e.g., Wertheimer, 1953; Elliott, 1960; Makeig and Inlow, 1993; Conte et al, 1995; Smith et al, 2003; Arruda et al, 2009; Aue et al, 2009). In particular, Monto et al (2008) have demonstrated that somatosensory detection performance and power in all frequency bands are correlated with the phase of infraslow fluctuations (0.1–0.01 Hz, i.e., 10–100 s cycles) of EEG, a finding that could be interpreted as reflecting slow variations in attentional state.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, some investigators reported that resting-state activation in the parietal region is consistently linked to an attention network and n-back performance [19], [33]–[35]. Activation in the right frontal and parietal regions have previously been linked to the engagement of visuospatial processing and selective attention [19], [33][39]. Additionally, neurophysiological measures of selective attention and cortical arousal (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, neurophysiological measures of selective attention and cortical arousal (e.g. larger delta/theta and beta power) are associated with WM performance and WM capacity [2], [13], [15], [39][43].…”
Section: Discussionmentioning
confidence: 99%